Desmodium amplistipulaceum (Leguminosae, Papilionoideae), a new species from northwest region of Chiapas, Mexico - Torres-Colín, Leticia; Alvarado-Cárdenas, Leonardo O. (Phytotaxa, 2019)
Desmodium amplistipulaceum, a new species from the evergreen tropical forest of La Sepultura Biosphere Reserve, Chiapas, is described and illustrated. Morphologically it is very similar to Desmodium helleri, but it differs from this by persistent and widely ovate stipules; inflorescences in simple racemes and slightly hirsute sessile loments with 4 or 5 articles. It includes a morphological description, map of distribution and comparative photographs of the calyx, trichomes of calyx and gynoecium and stigma for both species, as well as an identification key to differentiate all the Desmodium species from La Sepultura, Chiapas.